Sequentially tunable buckling in 3D printing auxetic metamaterial undergoing twofold viscoelastic resonances - Liu, Yuheng (2022)
With the development of metamaterials, tunable auxetic structures have attracted extensive attention due to their unusual mechanical behaviors. In this study, we design and 3D print an auxetic shape-memory dual-moiety structure, and achieve a reversible and sequential buckling behavior by means of the local instability. Effects of hollowness radius, Young's modulus ratio and temperature on the buckling behavior of this auxetic dual-moiety structure have been studied by the finite element method analysis. The constitutive relationships between stress, strain, hollowness radius and Young's modulus have been presented and discussed. Finally, the buckling behaviors have been investigated by the mechanical tests, and the accuracy of numerical results has then been verified by using the experimentally obtained data. This study is expected to provide a design guideline for auxetic dual-moiety structure with sequentially tunable buckling behaviors by means of twofold viscoelastic resonances.